2015
DOI: 10.21608/jbaar.2015.105963
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of some pesticides on the enzymatic activities and spermatogenesis of the land snail Monacha cantiana

Abstract: Laboratory studies have been carried out on the toxic effects of three different pesticides namely, Diazinon, Lambdacyhalothrin and Methomyl as poisonous baits against the land snail, Monacha cantiana. The activities of five vital tissue enzymes, as Catalase (CAT), Malondialdehyde (MDA), Aspartate transaminase (AST). Alanine transaminase(ALT) and Alkaline phosphatase (ALP) were examined after exposure of these snails to LC 50 (5ppm) of the tested pesticides for 96hr. Results showed clearly that all sublethal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…The present study revealed that Anatoxin-a and Glufosinate-ammonium significantly increased ALP levels in the digestive gland of treated M. cartusiana. Such increments are in harmony with the results of Sharaf et al (2015) who stated that Diazinon, Lambda-cyhalothrin, and Methomyl exposure increased ALP levels in M. cartusiana. This increase may be due to destruction of the hepatic cell.…”
Section: Biochemical Biomarker In Clover Snail M Cartusiana Exposed T...supporting
confidence: 88%
See 2 more Smart Citations
“…The present study revealed that Anatoxin-a and Glufosinate-ammonium significantly increased ALP levels in the digestive gland of treated M. cartusiana. Such increments are in harmony with the results of Sharaf et al (2015) who stated that Diazinon, Lambda-cyhalothrin, and Methomyl exposure increased ALP levels in M. cartusiana. This increase may be due to destruction of the hepatic cell.…”
Section: Biochemical Biomarker In Clover Snail M Cartusiana Exposed T...supporting
confidence: 88%
“…Such increment in CAT and GPX activities may be an adaptive mechanism to prevent the accumulation of toxic reactive oxygen (Regoli et al, 2006). In the same regard, Sharaf et al (2015) found that CAT activity increased in the digestive gland of the clover snail, M. cartusiana, after treatment with Diazinon, Lambda-cyhalothrin, and Methomyl. Glutathione-s-transferase (GST) plays a vital role in defending cells and tissues from oxidative stress (Havelková et al, 2008).…”
Section: Oxidative Stress and Antioxidant Biomarkers In Clover Snail ...mentioning
confidence: 93%
See 1 more Smart Citation
“…The present study revealed that Anatoxin-a and Glufosinate-ammonium significantly increased ALP levels in the digestive gland of treated M. cartusiana. Such increments are in harmony with the results of Sharaf et al (2015) who stated that Diazinon, Lambda-cyhalothrin, and Methomyl exposure increased ALP levels in M. cartusiana. This increase may be due to destruction of the hepatic cell.…”
Section: Biochemical Biomarker In Clover Snail M Cartusiana Exposed T...supporting
confidence: 88%
“…The current study displayed that MDA levels increased significantly in clover snail M. cartusiana after treatment with two pesticides. Likewise, Sharaf et al, (2015) illustrated that MDA levels increased in the clover snail, M. cartusiana, after exposure to Diazinon, Lambdacyhalothrin, and Methomyl. The increment may induce this elevation in free radicals, which causes the overproduction of MDA.…”
Section: Oxidative Stress and Antioxidant Biomarkers In Clover Snail ...mentioning
confidence: 95%